Pyrrolidine-based amino alcohols: novel ligands for the enantioselective alkylation of benzaldehyde - Gonsalves, António M. d'. A. Rocha (2003)
A series of easily obtained pyrrolidine-based [beta]-amino alcohols derived from tartaric acid and primary amines was synthesized and used as chiral ligands in the enantioselective alkylation of benzaldehyde. Using diethylzinc, 1-phenyl-1-propanol was obtained with enantiomeric excesses of up to 80% when (3S,4S)-N-(1-naphthylmethyl)-3,4-dihydroxypyrrolidine was used. The nature of the N-substituent on the ligand, as well as the reaction temperature proved to significantly influence reaction product distribution as well as the enantiomeric excess of the chiral alcohol.